2005
DOI: 10.1113/jphysiol.2004.078014
|View full text |Cite
|
Sign up to set email alerts
|

Lactate and force production in skeletal muscle

Abstract: Lactic acid accumulation is generally believed to be involved in muscle fatigue. However, one study reported that in rat soleus muscle (in vitro), with force depressed by high external K + concentrations a subsequent incubation with lactic acid restores force and thereby protects against fatigue. However, incubation with 20 mM lactic acid reduces the pH gradient across the sarcolemma, whereas the gradient is increased during muscle activity. Furthermore, unlike active muscle the Na + -K + pump is not activated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
68
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 23 publications
(30 reference statements)
4
68
2
Order By: Relevance
“…During the subsequent fatiguing stimulation period, the added lactic acid would hinder the export of lactate and hydrogen ions produced by glycogenolysis and in this way exaggerate the fatigue-induced acidification. Nevertheless, the addition of lactic acid did not have any marked effect on fatigue development in either soleus or EDL muscles, which agrees with recent results on rat soleus muscles (Kristensen et al 2005). Thus, these results support the conclusion that accumulation of lactate and hydrogen ions is not a major cause of fatigue (Pate et al 1995;Bangsbo et al 1996;Bruton et al 1998;Posterino et al 2001;Lamb, 2002;Westerblad et al 2002).…”
Section: Discussionsupporting
confidence: 82%
“…During the subsequent fatiguing stimulation period, the added lactic acid would hinder the export of lactate and hydrogen ions produced by glycogenolysis and in this way exaggerate the fatigue-induced acidification. Nevertheless, the addition of lactic acid did not have any marked effect on fatigue development in either soleus or EDL muscles, which agrees with recent results on rat soleus muscles (Kristensen et al 2005). Thus, these results support the conclusion that accumulation of lactate and hydrogen ions is not a major cause of fatigue (Pate et al 1995;Bangsbo et al 1996;Bruton et al 1998;Posterino et al 2001;Lamb, 2002;Westerblad et al 2002).…”
Section: Discussionsupporting
confidence: 82%
“…Previous studies (10,15,31,36,38) on K ϩ -induced inhibition of contractile force and the protective effects of Na ϩ -K ϩ pump stimulation and acidosis, have focused on slow-twitch muscles. Because a large fraction of skeletal muscles are composed of fast-twitch fibers, it was of interest to characterize the response of these fibers to high [K ϩ ] o , Na ϩ -K ϩ pump stimulation, and acidosis, in particular because in these fibers, excitation induces a much more pronounced loss of K ϩ than in slow-twitch fibers (14).…”
Section: Discussionmentioning
confidence: 99%
“…Recent in vitro studies (30,31,36) on slow-twitch muscles have shown that in these muscles, the depressing effect of high [K ϩ ] o on excitability and contractility can also be counteracted by lactic acid. The effect on excitability is secondary to the ensuing reduction in muscle pH and might be related to an inhibitory effect of acidosis on the chloride conductance (38,39).…”
mentioning
confidence: 99%
“…This view is not recognised by all. By contrast, Kristensen et al (2005) questioned whether this phenomenon can be extended to a whole-system model during exercise. These authors reported that muscle preparations in vitro were unable to produce a similar amount of force compared with controls when incubated in a 20·mmol·l -1 Na-lactate, 12·mmol·l -1 Na-lactate + 8·mmol·l -1 lactic acid or a 20·mmol·l -1 lactic acid solution and stimulated to fatigue.…”
Section: Lactate As the Cause Or Consequence Of Fatigue?mentioning
confidence: 99%